Problem-Based Mathematics Learning to Analyze The Mathematical Literacy Ability of VIII Class Students Reviewed Based on Minimum Competence Assessment Type (AKM) - Lawalata, Daystera J.; Rudhito, Marcellinus A. (Universitas Sebelas Maret, 2023)
This study aims to determine the trajectory of learning that is oriented towards mathematical literacy skills and to find out the results of learning that are oriented towards mathematical literacy abilities with problem-based learning in terms of AKM-type questions. This type of research is design research, descriptive model. The research subjects were 20 students in the experimental class and 7 students in the research class. The results of the study were obtained by carrying out 2 learning meetings and 1 meeting for the test. In general, the steps of the research carried out are: (1) provide real problems related to opportunity material on the topic of sample space and sample points, (2) provide problems related to opportunity material on the topic of opportunity events, (3) provide a final test in the form of real problems presented with the AKM type. The learning outcomes after undergoing a problem-based mathematics learning process are: (1) Students can mention the sample space and sample point of an event, (2) students can mention the formula for the probability of an event and the probability of not happening, (3) Students have not fulfilled the 3 basic competencies of mathematical literacy.